A two-echelon inventory model for a deteriorating item with stock-dependent demand, partial backlogging and capacity constraints - Ghiami, Yousef; Williams, Terry; Wu, Yue (European Journal of Operational Research, 2013)
This study investigates a two-echelon supply chain model for deteriorating inventory in which the retailer's warehouse has a limited capacity. The system includes one wholesaler and one retailer and aims to minimise the total cost. The demand rate in retailer is stock-dependent and in case of any shortages, the demand is partially backlogged. The warehouse capacity in the retailer (OW) is limited; therefore the retailer can rent a warehouse (RW) if needed with a higher cost compared to OW. The optimisation is done from both the wholesaler's and retailer's perspectives simultaneously. In order to solve the problem a genetic algorithm is devised. After developing a heuristic a numerical example together with sensitivity analysis are presented. Finally, some recommendations for future research are presented. © 2013 Elsevier B.V. All rights reserved.